MEMO: Middle Leadership Academy Disenrollment Process Report - Anna Benscoter:::Manger, Student Business Services:::; Ernesto Guerrero:::Special Assistant to the Vice President for Student Affairs::: (2022)
A six-person Channel Island's team was convened in May 2021 and was asked to take part in the CSU Sponsored Middle Leadership Academy (MLA). This professional and leadership development program used a project-based format to engage collaborative, cross-divisional campus teams to design and implement equity projects that sought to address and improve student success. Our team was tasked by campus leadership to review the process of disenrollment of students for nonpayment and to determine if there was a disproportional impact on historically underrepresented groups.The issue we were tasked to address was the disenrollment of students for nonpayment and the subsequent impact of that on historically underrepresented groups. Initially, our assumption was that there was something inherently wrong or overly cumbersome about our disenrollment process.